Differences in glucose yield of residues from among varieties of rice, wheat, and sorghum after dilute acid pretreatment*. Issue 8 (3rd August 2017) - Teramura, Hiroshi; Sasaki, Kengo; Kawaguchi, Hideo; Matsuda, Fumio; Kikuchi, Jun; Shirai, Tomokazu; Sazuka, Takashi; Yamasaki, Masanori; Takumi, Shigeo; Ogino, Chiaki; Kondo, Akihiko
Abstract : Bio-refinery processes require use of the most suitable lignocellulosic biomass for enzymatic saccharification and microbial fermentation. Glucose yield from biomass solid fractions obtained after dilute sulfuric acid (1%) pretreatment (at 180 °C) was investigated using 14, 8, and 16 varieties of rice, wheat, and sorghum, respectively. Biomass solid fractions of each crop showed similar cellulose content. However, glucose yield after enzymatic hydrolysis (cellulase loading at 6.6 filter paper unit/g-biomass) was different among the varieties of each crop, indicating genotypic differences for rice, wheat, and sorghum. Nuclear magnetic resonance method revealed that the high residual level of lignin aromatic regions decreased glucose yield from solid fraction of sorghum. Abstract :